"Hostages to Compliance": Towards a Reasonableness Test for Administrative Burdens. Issue 4 (18th April 2020) - Doughty, Meghan; Baehler, Karen J
Abstract: Administrative burden on its most basic level refers to "an individual's experience of policy implementation as onerous". The concept of administrative burdens raises complex questions of both theory and practice for public administrators and scholars. Ambitious agendas have been laid out for investigating the origins, mechanisms, and impacts of administrative burdens, and for building practical knowledge about how to minimize administrative burdens without sacrificing program effectiveness and efficiency. Those same authors, and others, have advanced the concept theoretically as well. This article builds on those efforts to address a normative question at the concept's core—namely, the question of what makes an administrative burden acceptable or excessive, reasonable or unreasonable. Our inquiry begins with the recognition that administrative burdens sometimes perform important functions and principles and methods are needed for determining when a specific type or degree of burden crosses the threshold from reasonableness to unreasonableness. Toward that end, we propose a five-part test, similar to those employed by the Supreme Court, for bureaucrats to use when assessing the justifications for bureaucratic procedures and requirements that involve administrative burden.